Bowen ratio estimates in green house and open field conditions of the University of the Philippines Los Baños - Gallegos, Ralph Kristoffer B.; Saludes, Ronaldo B.; Paras, Fernando O. Jr. (2013)
Bowen ratio (B) estimates were determined inside the Pamana Greenhouse and in the open field of the National Agromet Station (NAS) of the University of the Philippines Los Baños. The experiment involved the use of temperature and relative humidity loggers to estimate the Bowen ratio. It was observed that the diurnal temperature and relative humidity variations in the open field were greater compared to variations inside the greenhouse. This confirmed the observation that the greenhouse environment is more uniform and stable compared to the ambient. Similarly, the Bowen ratio was more variable in the open field (NAS) compared to the Pamana Greenhouse. Average Bowen ratio values of B = 0.47 for the NAS open field and B = 0.21 for the Pamana Greenhouse were computed. By using suitable radiation fluxes instruments, verification of these estimates was recommended to determine their accuracy.
Keywords: Greenhouse management; Environmental protection